Legal Protection Against a Mother Who Has Baby Bluess - Tarisah, Atasa; Handayani, Trini; Mulyana, Aji (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
Postpartum mothers who suffer from baby blues syndrome may abuse their biological children. Baby blues syndrome is a form of mental disorder. The chronology, mental condition, evidence and results of forensic psychiatry in a case of abuse by a perpetrator who suffers from a mental disorder are very important considerations and determine whether or not the perpetrator can be punished. This is considering that apart from the Criminal Code, regulations regarding legal accountability for perpetrators of mental disorders are also regulated in Law of the Republic of Indonesia Number 36 of 2009 concerning Health (UU Health) and Law of the Republic of Indonesia Number 18 of 2014 concerning Mental Health (UU Mental Health ). This research also explores the form of legal responsibility for the perpetrator. This research methodology uses normative juridical, with a statutory regulation approach and a case approach. Data collection was obtained using the data analysis method in the form of descriptive qualitative analysis of secondary data. The results of the research show that perpetrators suffering from baby blues syndrome when committing abuse cannot be punished due to forgiving reasons based on Article 44 paragraph (1) of the Criminal Code which is an exception for mental disabilities for the mental disorders they suffer from. Criminal liability certainly cannot be imposed on the perpetrator. The form of legal responsibility is carrying out rehabilitation as well as efforts to cure it, as well as carrying out education regarding the mental illness suffered.